EFFECT OF SCREW CONVEYOR SPEED AND CUTTER DIAMETER ON THE PRODUCTION PERFORMANCE OF MEATBALL FORMING MACHINE - Siti Duratun Nasiqiati Rosady; Fitrah Bisma Taimullah Al Jahfal; Ardhi Prawira Rohim; Talifatim Machfuroh; Zakiyah Amalia; Fica Aida Nadhifatul Aini (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Manual meatball production in small and medium enterprises often results in inconsistent product mass and low production efficiency. This study aims to analyze the effect of screw conveyor speed and cutter diameter on the production performance of an automatic meatball forming machine. The experiment was conducted at the Mechanical Engineering Laboratory, Politeknik Negeri Malang, using the Design of Experiment (DOE) factorial method. The independent variables were screw conveyor speed (159 rpm, 186 rpm, and 236 rpm) and cutter diameter (15 mm, 20 mm, and 25 mm), while the dependent variables were the produced meatball mass and production capacity. Data were analyzed using Minitab 21 software with a Two-Way ANOVA test to evaluate the influence of the main factors and their interaction on the output. The results show that both independent variables significantly affect the meatball mass (p-value < 0.05). Higher screw conveyor speeds increased meatball mass but reduced the number of meatballs produced, while larger cutter diameters generated heavier meatballs with lower production capacity. Response optimization analysis revealed the best combination at a screw speed of 124 rpm and a cutter diameter of 30 mm, yielding a desirability value of 0.93. This configuration produced meatballs within the optimal weight range of 15–25 grams with minimal power consumption. It can be concluded that the precise adjustment of screw conveyor speed and cutter diameter significantly improves product uniformity, machine performance, and production efficiency, supporting productivity enhancement in small-scale food manufacturing industries.